Multiscale Ecological Zoning Management with Coupled Ecosystem Service Bundles and Supply–Demand Balance, the Case of Hangzhou, China - Yonghua Li; Xinyi Ding; Song Yao; Bo Zhang; Hezhou Jiang; Junshen Zhang; Xinwei Liu (Land, 2024)
Grasping the interrelationship between the supply and demand of ecosystem services (ESs) and spatial scale characteristics is the foundation for effective ecological zoning management, which helps to realize a win–win situation for both ecological protection and economic development. This paper focuses on the following three real problems: mismatch in ES supply and demand evaluation, mechanical and subjective delineation of ecological zoning, and rough management strategies, and constructs a multi-scale ecological zoning management framework for the “comprehensive evaluation of supply and demand, ecological zoning, and enhancement of human well-being”. This study integrates the InVEST model, SOM, Z-score quadrant matching, and coordination degree method, and applies them to the ecological management zoning of Hangzhou. The results show that (1) the spatial differentiation of ESs in Hangzhou is significant. The spatial pattern of the five types of ES supply varies at the county scale and the grid scale on which ES demand is concentrated and is consistent at different scales. (2) ES supply–demand matching in Hangzhou is at the basic coordination and can be divided into four modes including HH, LH, LL, and HL at both the county and grid scales. On the small scale, the proportion of mismatches declines slightly, but the severity rises. (3) ES supply is divided into four categories as follows: the food production bundle, the carbon storage bundle, the ESs balancing bundle, and the ESs depleting bundle, and clarifies the priority of ES management. (4) Construct an ecological management practice path, delineates 6 ecological management zones at the county scale and 19 secondary management zones at the grid scale. Targeted measures are proposed in terms of supply–demand adjustment strategies, ecological management strategies, and key implementation areas. This study helps to incorporate the interaction between the supply and demand of ESs into the planning framework and provides decision-making support for refined ecological management.